Релігійне життя населення Волинської області в 1964–1985 рр. - Savytska, Ilona; Савицька, Ілона (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Проаналізовано антирелігійну політику влади, висвітлено її особливості на Волині та способи й методи втілення. Досліджено становище православних громад і протестантських об’єднань області. Особливу увагу приділено динаміці змін у релігійній мережі та обрядовості (на основі низки архівних документів).On the basis of archival documents and published material critical thinking in the paper analyzes the anti-religious policy of the authorities, the ways and methods of implementation. Found that the region 1964-1985 government policy with regard to the church was more liberal in comparison with the previous period. In this case, anti-church campaign in the Volyn region had its own peculiarities. After all, the traditional feature of the spiritual life of Volyn was the priority of religious values in the political dogmas that determined the strong position of the church institutions in the region. Investigated the situation of the Orthodox and Protestant communities, associations of the region. Studied the position of the Protestant associations, which were interpreted as sectarian Soviets. In the analyzed period the Volyn region of the main Protestant communities took place Evangelical Christian Baptists (ECB) and the Pentecostals. In the act Baptist congregation dissenters, Jehovah's Witnesses.
The Religious Life of the Population in the Volyn Region 1964–1985
Keywords: антирелігійна політика; православні громади; протестантські об’єднання; атеїстична пропаганда; релігійна обрядовість; anti-religious policy; the Orthodox community; the Protestant Association; atheist propaganda; religious rites